Tingkat Kondisi Fisik Pemain Futsal Putra di MA Negeri 1 Mataram Tahun 2026 - Muhammad Bakhtiar Misbah; Dadang Warta Chandra Wira Kesuma; Indri Susilawati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Physical condition is a key factor determining futsal players' performance, as matches are played at high intensity and demand optimal aerobic and anaerobic capabilities. However, the physical condition profiles of school-level futsal athletes are rarely comprehensively evaluated to serve as a basis for training program design. This study aims to describe the physical condition levels of male futsal players at MAN 1 Mataram. A quantitative approach with a descriptive design was employed. The sample consisted of 16 players selected using total sampling. Data collection involved the Multistage Fitness Test (MFT) to measure VO₂Max, a 30-meter sprint test, the Illinois agility test, a 60-second push-up test, and a vertical jump test. Data were analyzed using descriptive statistics specifically mean values ​​and percentages based on the norms for each test instrument. The results showed that leg muscle explosive power averaged 51.56 cm (predominantly